KONSTRUKSI PENDIDIKAN HUMANISTIK: DIALOG TEACH LIKE FINLAND DAN NILAI NORMATIF ISLAM DI INDONESIA - Iqbal Ramadhan Irsyad Yudiono; Fadel Ikhlasul Amal; Miftahul Ramadani; Sani Jamilatus Solihah; Tiara Hezrine Masytah; Bustaniyatuz Zahra Ramadhani; Zaky Zaidul Mubarok; Fauzi Annur (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2025)
ABSTRACT Education is fundamentally aimed not only at improving students’ academic abilities but also at fostering psychological well-being, emotional balance, and holistic human development. However, contemporary educational practices still tend to position grades, competition, and standardized assessments as the primary indicators of learning success, causing the humanistic dimension of education to be frequently overlooked. This study aims to analyze the construction of humanistic education through a conceptual dialogue between the pedagogical ideas presented in Teach Like Finland by Timothy D. Walker and Islamic educational values, as well as to examine their relevance to the implementation of the Merdeka Curriculum in Indonesia. This research employed a qualitative approach using a library research method. The research data were collected through literature searches on Google Scholar, SINTA, and GARUDA, and then analyzed using content analysis techniques through the stages of theme identification, concept categorization, interpretation, and contextual meaning construction. The findings indicate that student well-being holds a fundamental role in creating meaningful and sustainable learning experiences. In addition, pedagogical autonomy and the strengthening of collaborative relationships among students were found to contribute to a more inclusive learning environment with lower psychological pressure. This study also reveals that integrating humanistic educational concepts with the principle of al-adab qabla al-‘ilm can strengthen the implementation of the Merdeka Curriculum by emphasizing character development, mental health, and holistic human growth. ABSTRAK Pendidikan pada dasarnya tidak hanya diarahkan untuk meningkatkan kemampuan akademik peserta didik, tetapi juga membangun kesejahteraan psikologis, keseimbangan emosional, dan kualitas kemanusiaan secara utuh. Namun, praktik pendidikan modern masih cenderung menempatkan capaian nilai, kompetisi, dan evaluasi terstandar sebagai ukuran utama keberhasilan belajar sehingga dimensi humanistik sering terabaikan. Penelitian ini bertujuan menganalisis konstruksi pendidikan humanistik melalui dialog konseptual antara gagasan pedagogis dalam buku Teach Like Finland karya Timothy D. Walker dan nilai-nilai pendidikan Islam, serta mengidentifikasi relevansinya terhadap implementasi Kurikulum Merdeka di Indonesia. Penelitian menggunakan pendekatan kualitatif dengan jenis studi kepustakaan (library research). Data penelitian diperoleh melalui penelusuran literatur pada Google Scholar, SINTA, dan GARUDA, kemudian dianalisis menggunakan teknik content analysis melalui tahapan identifikasi tema, kategorisasi konsep, interpretasi, dan penarikan makna kontekstual. Hasil penelitian menunjukkan bahwa kesejahteraan siswa (well-being) memiliki posisi mendasar dalam menciptakan pembelajaran yang bermakna dan berkelanjutan. Selain itu, kebebasan pedagogis dan penguatan relasi kolaboratif antarpeserta didik terbukti mampu membangun lingkungan belajar yang lebih inklusif dan minim tekanan psikologis. Penelitian ini juga menemukan bahwa integrasi konsep pendidikan humanistik dengan prinsip al-adab qabla al-‘ilm dapat memperkuat implementasi Kurikulum Merdeka agar lebih berorientasi pada pengembangan karakter, kesehatan mental, dan pertumbuhan manusia secara holistik